Regulatory issues. - Munzner, R. (IEEE Engineering in medicine and biology magazine)
The medical device amendments of 1976 to the Food, Drug and Cosmetic Act created three levels regulation for devices: Class 1, General Controls: meaning that only the general provisions of the Act would be needed by the FDA to control the safety and effectiveness of devices in this class. General controls include premarket notification, good manufacturing practices, truth in labeling, and adequate directions for use. Class 11, Performance Standards: which was later redefined as Special Controls, meaning that the FDA would need to apply special rules for particular devices to assure safety and effectiveness of those devices. The general controls also apply. Class III, Premarket Approval: meaning an application (PMA) to market the device would be submitted to the FDA and that the device could not be marketed unless the application was approved. General controls also apply, and special controls might also apply.